Urban water distribution networks : assessing systems vulnerabilities, failures, and risks - Christodoulou, Symeon; Fragiadakis, Michalis; Agathokleous, Agathoklis; Xanthos, Savvas (Butterworth-Heinemann, 2018)
Urban Water Distribution Networks: Assessing Systems Vulnerabilities and Risks provides a methodology for a system-wide assessment of water distribution networks (WDN) based on component analysis, network topology and, most importantly, the effects of a network's past performance on its seismic and/or non-seismic reliability. Water distribution networks engineers and system designers face multiple operational issues in delivering safe and clean potable water to their customers.